Risk Factors for de Quervain Syndrome Among Fermented Cassava Processing Workers: A Descriptive Study in Jember, Indonesia - Faihaa Jannatuz Zahro; Ana Islamiyah Syamila; Ragil Ismi Hartanti (Journal of Public Health for Tropical and Coastal Region, 2026)
Introduction: De Quervain syndrome is characterized by chronic inflammatory pain resulting from the overuse of the joints around the thumb and wrist. Cassava processing workers require various repetitive movements in their work activities and are at risk experience de Quervain syndrome. This study aims to provide an overview of the risk factors for de Quervain syndrome among workers in the fermented cassava processing industry.Methods: The research was conducted quantitatively with descriptive methods in industries A, B, C, and D in Jember Regency. The Visual Analogue Scale for Pain (VAS) was used to measure the pain experienced by workers, while the Assessment of Repetitive Tasks (ART) tools for upper limbs were used to assess the results of repetitive movement exposure in the work process.Results: The results showed that de Quervain symptoms were mostly experienced by workers on the right hand (65.7%), with symptoms of pain during movement. The proportion of symptoms on the right hand was mostly felt by workers aged ≥55 years (100%), female (87.5%), heavy-fat BMI (100%), working for >5 years (70%), >8 hours/day (66.7%), and doing repetitive motion >20 times/minute (70%).Conclusion: Most of the fourth workers experienced de Quervain symptoms on the right hand as many as 23 people, while 17 people felt it on the left hand. Future researchers are expected to be able to measure de Quervain's complaints objectively through the Finkelstein test.